Rat model of congenital toxoplasmosis. - Dubey, J P (1991)
A rat model of congenital toxoplasmosis is described for the study of protective immunity and chemotherapy during pregnancy. Six Sprague-Dawley 7- to 15-day gestational rats were inoculated orally (three rats, trial A) or subcutaneously (three rats, trial B) with 10,000 infective oocysts of the CT-1 strain of Toxoplasma gondii. The tissues of rat pups born from these rats were bioassayed for T. gondii infection. T. gondii was recovered from 30 of 33 (90.9%, trial B) and 23 of 28 (82.17%, trial A) rat pups bioassayed at 1 to 134 days of age. Two 10- to 14-day gestational pregnant rats were inoculated subcutaneously (trial C) with 10,000 infective bradyzoites from tissue cysts; 10 of 23 (43.8%) of the newborn pups were infected with T. gondii. Congenital infection occurred only when rats were infected during pregnancy. None of three rats in trial A that had given birth to congenitally infected rat pups produced congenitally infected rat pups during the second pregnancy.